Evidence Graph Analysis of Postoperative Pain Sensitization Induced by Perioperative Sleep Deprivation - XUE Jianjun; WANG Caihong; GUO Lingling; LI Xiuxia; ZHANG Jie; XU Ziqing; HOU Huaijing; YANG Kehu (Xiehe Yixue Zazhi)
ObjectiveTo describe and evaluate the clinical studies of postoperative pain sensitization caused by sleep deprivation through the evidence map system, understand the distribution of evidence in this field, and provide reference for subsequent evidence research.MethodsA computer-based search of PubMed, EMBASE, Cochrane library, Web of Science, CNKI, Wanfang Data, VIP and Chinese Biomedical Literature Database from inception to August 2023 was conducted to obtain intervention studies, observational studies and systematic reviews/Meta-analysis of postoperative pain sensitization caused by sleep deprivation. The research characteristics and methodological quality were analyzed and evaluated. The Cochrane Handbook for Systematic Reviews, the Newcastle-Ottawa Scale (NOS) and the AMSTAR-2 scale were used to evaluate the quality of the included studies, and the evidence was comprehensively analyzed and displayed by means of bubble chart, table and text.ResultsA total of 35 observational studies (31 cohort studies and 4 case-control studies), 15 randomized controlled trials and 4 systematic reviews/Meta-analyses were included. The number of publications increased rapidly after 2018 and peaked in 2022, and clinical studies in this field mainly focused on cohort studies, with fewer randomized controlled trials and systematic reviews/Meta-analysis studies. The results of the evidence map showed that in terms of quality, 22 studies were 'high quality', 24 studies were 'medium quality', and 8 studies were 'low quality'.Thirty studies showed that sleep deprivation could induce postoperative pain sensitization. Only 2 studies suggested that sleep disorders were not significantly associated with postoperative pain sensitization, and ten studies were uncertain whether sleep deprivation could induce postoperative pain sensitization.ConclusionsOverall evidence shows that sleep deprivation can induce postoperative pain sensitization, but the evaluation dimensions are limited and the methodological quality of the included literature needs to be improved. More high-quality, large-sample and standardized clinical studies should be carried out in the future to provide better scientific basis for clinical work.